Screening of Pine Needle's Extractives Against Wood and Bamboo Decaying Fungi - Sumi, A.; Tripathi, S.; Harsh, N. S. K. (Indian Forester, 2015)
Extractives from the pine needles (Pinus roxburghii. Sarg.) are rich in resin and essential oil and are effective in protecting wood and bamboo products. This study was conducted to evaluate the efficacy of pine needle's extractives at different concentrations against white rot (Trametes versicolor L. ex Fries.), brown rot (Oligoporus placentus. Murr.) and some common bamboo decaying fungi-Xylaria acuminata Hill. ex Schrank. and Hypochnicium punctulatum (Cooke) J. Erikss. by malt-agar bioassay with an objective to screen its activity as preservative. Results revealed an effectiveness of pine needle's extractivein inhibiting the growth of the decaying fungi completely at low concentration.